Local Political Democratization Policy: Voter Participation in the Direct Regional Head Elections - Winengan Winengan (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The regional head election, a local political event and a symbol of democratic government, is a contest for a legitimized power of regional leaders, who are given authority and responsibility to administer and lead the regional apparatus and development. Since the Indonesian reformation era, the policy regarding the regional head election has shifted from being elected by the local legislative assembly (representative system) to being elected by the people directly (direct election). Anchored in the quantitative descriptive research design, in which the data was garnered from documentation, this study aims to examine the extent to which the people partook in the first round of the direct and simultaneous regional head election in 2015. The collected data was analyzed by means of the participatory and democracy approach within the local political landscape. The empirical findings showed that the public participation in the local election remained low given the statistical evidence (64.02% of the total voters). The study demonstrates that despite the provision of the political stage within the local scope, it does not fully encourage the people to exercise their political rights.